Function Analysis of MBF1, a Factor Involved in the Response to Amino Acid Starvation and Virulence in Candida albicans - Amorim-Vaz, Sara; Coste, Alix T.; Tran, Van Du T.; Pagni, Marco; Sanglard, Dominique (Frontiers in Fungal Biology, 2021)
Candida albicans is a commensal of human mucosae, but also one of the most common fungal pathogens of humans. Systemic infections caused by this fungus, mostly affecting immunocompromised patients, are associated to fatality rates as high as 50% despite the available treatments. In order to improve this situation, it is necessary to fully understand how C. albicans is able to cause disease and how it copes with the host defenses. Our previous studies have revealed the importance of the C. albicans gene MBF1 in virulence and ability to colonize internal organs of mammalian and insect hosts. MBF1 encodes a putative transcriptional regulator, and as such it likely has an impact in the regulation of C. albicans gene expression during host infection. Here, recent advances in RNA-seq technologies were used to obtain a detailed analysis of the impact of MBF1 on C. albicans gene expression both in vitro and during infection. MBF1 was involved in the regulation of several genes with a role in glycolysis and response to stress, particularly to nutritional stress. We also investigated whether an interaction existed between MBF1 and GCN4, a master regulator of response to starvation, and found that both genes were needed for resistance to amino acid starvation, suggesting some level of interaction between the two. Reinforcing this idea, we showed that the proteins encoded by both genes could interact. Consistent with the role of MBF1 in virulence, we also established that GCN4 was necessary for virulence in the mouse model of systemic infection as well as in the Galleria mellonella infection model.